Perbandingan Pemahaman Konsep Siswa dengan Menggunakan Model Pembelajaran Contextual Teaching And Learning dan Penemuan Terbimbing Di Kelas VIIMts.S Al-Jihad Medan - Raja Sofiyah Nasution; Syafari . . (Universitas Negeri Medan, 2018)
This study aims to determine whether there is a difference in the ability to understand students'concepts taught by using Contextual Teaching And Learning (CTL) learning model and studentstaught with guided invention learning model at MTs.S Al-Jihad Medan. This study was designedand implemented using a quasi-experimental method and involved a sample of 60 students. Thisstudy uses the instrument in the form of a description of pretest and posttest used to determinethe ability of understanding the concept of mathematics students. From the research result, itcan be found the postest average value 81,33 for experiment class A and 78,4 for experimentclass B. The data obtained are analyzed by using Chi-Square test, F test, and t test. Based onthe test, it can be concluded that there is a difference of students' concept comprehension abilitytaught by using Contextual Teaching And Learning (CTL) learning model and students taughtby Guided Discovery model at MTs.S Al-Jihad MedanT.A 2017/2018.